Basics of verbal aspect in biblical Greek - Campbell, Constantine R. 1975- (Grand Rapids, Michigan Zondervan Academic, 2024)
"Basics of Verbal Aspect in Biblical Greek, Second Edition, by Constantine R. Campbell provides an accessible introduction to verbal aspect for students of New Testament Greek"--
Includes bibliographical references and index
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Bible -- Language, style; Greek language, Biblical -- Verb; Greek language, Biblical -- Aspect; RELIGION / Biblical Reference / Language Study; RELIGION / Biblical Reference / Handbooks